OVERVIEW OF PUBLIC PRIVATE PARTNERSHIPS IN AUSTRALIA: FINANCING, REGULATION, AUDITING AND PROPOSED IMPROVEMENTS - Taseska, Anita (The journal of contemporary issues in business and government, 2008)
The ideological demands for public authorities to concentrate on the perceived core competencies of their staff and to seek cost efficient operations has led to the emergence of a number of new philosophies which have appeared under various terms including the New Public Management, the public governance paradigm, public value model and the Best Value model (Talty, 2007). Public private partnerships (PPPs) are perceived to be one of the ways to achieve efficiencies in the provision of services to the public through outsourcing entire projects and their cost to private sector organisations. However, the lack of substantial and structured performance review, especially in the post-contracting stage, means that future PPP projects will not be able to systematically implement lessons learnt from past experiences. The overall conclusion from the literature suggests that the net benefits of PPPs are, so far, still subject to debate and uncertainty, and the absence of a coherent review process will limit improvement in their creation and management.